The "Parzival" of Wolfram von Eschenbach Translated into English Verse with Introduction, Notes, Connecting Summaries - Zeydel, Edwin H. (UNC Studies in the Germanic Languages and Literatures, 1951)
Originally published in 1951, this collaboration of two accomplished translators resulted in the first English verse translation of a major work of German literature. Rather than a translation of the entire poem, in this volume the translators present key passages connected by prose summaries, and include an introduction giving an overview of the work and its historical and literary context.